The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-79048/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Therapeutic Probiotics on Modulation of microRNAs

Abstract: Probiotics are beneficial bacteria that exist within the human gut, and which are also present in different food products and supplements. They have been investigated for some decades, due to their potential beneficial impact on human health. Probiotics compete with pathogenic microorganisms for adhesion sites within the gut, to antagonize them or to regulate the host immune response resulting in preventive and therapeutic effects. Therefore, dysbiosis, defined as an impairment in the gut microbiota, could pla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Interplays between microbiota and miRNAs have been reported in several lung diseases 62 , implicating the beneficial effects of probiotics on the modulation of miRNAs. Thus, the administration of probiotics may function through several signaling pathways, resulting in the prevention and treatment of various pathological conditions 63 . As microbiome dysbiosis is linked with the severity of COVID-19, the implication of probiotics in modulating the severity has been suggested as a promising weapon against COVID-19 24,25, 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Interplays between microbiota and miRNAs have been reported in several lung diseases 62 , implicating the beneficial effects of probiotics on the modulation of miRNAs. Thus, the administration of probiotics may function through several signaling pathways, resulting in the prevention and treatment of various pathological conditions 63 . As microbiome dysbiosis is linked with the severity of COVID-19, the implication of probiotics in modulating the severity has been suggested as a promising weapon against COVID-19 24,25, 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Most miRNAs are transcribed as precursors (either pri-miRNA or pre-mRNA) before capping and polyadenylation, and their biogenesis requires several enzymes, including Drosha, DGCR8, Dicer, and Argonaute (Ago) 2 ( Donker et al, 2007 ). In recent years, the remarkable roles of miRNAs in cellular proceedings under healthy or diseased conditions have been increasingly recognized ( Aghdam et al, 2019 ; Mirzaei and Hamblin, 2020 ; Sadri Nahand et al, 2020 ; Davoodvandi et al, 2021 ; Razavi et al, 2021 ). In particular, several studies have shown that knocking out the key enzymes in the miRNA processing results in embryonic arrest or even embryonic death ( Bernstein et al, 2003 ; Alisch et al, 2007 ; Suh et al, 2010 ), indicating the significance of miRNAs in the regulation of pregnant process.…”
Section: Introductionmentioning
confidence: 99%